1997
DOI: 10.1007/bf01277662
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of catecholamines and indoleamines in the cerebrospinal fluid of patients with vascular parkinsonism compared to Parkinson's disease patients

Abstract: The concentration of catecholamines and indoleamines in the cerebrospinal fluid of patients with vascular parkinsonism (VP) was compared to that in patients with Parkinson's disease (PD) and controls. Compared to the controls, the concentration of tyrosine was significantly higher, and the concentration of L-dopa and 3-O-methyldopa (3-OMD) was significantly lower in both VP and PD patients. The balance between the 3-OMD/L-dopa and dopamine (DA)/L-dopa ratios was changed in favor of 3-OMD/L-dopa in both VP pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…Tohgi et al (1991b, 1997) found a significant increase in tyrosine, and a significant decrease in CSF levodopa, DA, and 3-OMD in PD patients, which was related with levodopa dosage, and described an additional decrease in 3-OMD in subjects treated with tolcapone (Tohgi et al, 1995a). Other authors reported increased CSF 3-OMD related with levodopa therapy (Antkiewicz-Michaluk et al, 1997; Krygowska-Wajs et al, 1997).…”
Section: Neurotransmitters Neuromodulators and Related Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tohgi et al (1991b, 1997) found a significant increase in tyrosine, and a significant decrease in CSF levodopa, DA, and 3-OMD in PD patients, which was related with levodopa dosage, and described an additional decrease in 3-OMD in subjects treated with tolcapone (Tohgi et al, 1995a). Other authors reported increased CSF 3-OMD related with levodopa therapy (Antkiewicz-Michaluk et al, 1997; Krygowska-Wajs et al, 1997).…”
Section: Neurotransmitters Neuromodulators and Related Substancesmentioning
confidence: 99%
“…Tohgi et al (1993b,c, 1997) reported a 15–20% reduction of CSF 5-HT, tryptophan (precursor of 5-HT), kynurenine and 3-hydroxykynurenine (metabolites of tryptophan) levels in PD patients. CSF 5-HT levels showed a negative correlation with the severity of bradykinesia, rigidity and freezing of the gait, and decreased after levodopa therapy.…”
Section: Neurotransmitters Neuromodulators and Related Substancesmentioning
confidence: 99%
“…brain tissue 22,23 and nM in the CNS. 24 The distribution of catecholamines in the brain is not uniform. For example, dopamine concentration is particularly high in the basal ganglia, 25 a region where C. neoformans is often found.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, subchronic exposure of rats to low doses of TCDD is shown to produce larger changes in the levels of some biogenic amines and their metabolites in the brain, than the previously observed after acute exposure (Tuomisto et al, 1990). Since changes in the levels of biogenic amines are known to be associated with various human diseases (D'Amato et al, 1987;Hastings and Zigmond, 1997;Hornykiewicz, 1975;Okado et al, 2001;Richelson, 1991;Tohgi et al, 1997), these results may indicate possible long term neurotoxic effects of TCDD.…”
Section: Discussionmentioning
confidence: 59%